Nimodipine systemic exposure and outcomes following aneurysmal subarachnoid hemorrhage: a pilot prospective observational study (ASH-1 study) - Mahmoud, Sherif Hanafy; Hefny, Fatma; Isse, Fadumo Ahmed; Farooq, Shahmeer; Ling, Spencer; O'Kelly, Cian; Kutsogiannis, Demetrios James (Frontiers in Neurology, 2024)
Background: Nimodipine improves outcomes following aneurysmal subarachnoid hemorrhage (aSAH). Guidelines recommend that all patients receive a fixed-dose nimodipine for 21 days. However, studies reported variability of nimodipine concentrations in aSAH. It is not clear if reduced systemic exposure contributes to worsening outcomes. The aim of this study was to compare nimodipine systemic exposure in those who experienced poor outcomes to those who experienced favorable outcomes. Methods: This was a pilot prospective observational study in 30 adult patients admitted to the University of Alberta Hospital with aSAH. Data were collected from the electronic health records following enrolment. Blood samples were collected around one nimodipine 60 mg dose at steady state and nimodipine [total, (+)-R and (-)-S enantiomers] plasma concentrations were determined. Poor outcome was defined as modified Rankin Scale (mRS) at 90 days of 3-6, while favorable outcome was mRS 0-2. Correlation between nimodipine concentrations and percent changes in mean arterial pressure (MAP) before and after nimodipine administration were also determined. Furthermore, covariates potentially associated with nimodipine exposure were explored. Results: 20 (69%) participants had favorable outcomes and 9 (31%) had poor outcome. Following exclusion of those with delayed presentation (>96h from aSAH onset), among those presented with World Federation of Neurological Surgeons (WFNS) grade 3-5, nimodipine median (interquartile range) area under the concentration time curve (AUC0-3h) in those with favorable outcome were 4-fold higher than in those with poor outcome [136(52-192) vs. 33(23-339) ng.h/mL, respectively, p-value=0.2] . On the other hand, among those presented with WFNS grade 1-2, nimodipine AUC0-3h in those with favorable outcome were significantly lower than in those with poor outcome [30(28-36) vs. 172(117-308) ng.h/mL, respectively, p-value=0.03)]. (+)-R-nimodipine AUC0-3h in those who did not develop vasospasm were 4-fold significantly higher than those who had vasospasm (p-value=0.047). (-)-S-nimodipine only was significantly correlated with percentage MAP reduction. Similar results were obtained when the whole cohort was analyzed. Conclusions: The study was the first to investigate the potential association between nimodipine exposure following oral dosing and outcomes. In addition, it suggests differential effects of nimodipine enantiomers, shedding the light on the potential utility of nimodipine enantiomers. Larger studies are needed.